A 1 V -21 dBm threshold voltage compensated rectifier for radio frequency energy harvesting - Seyed Arash Zareianjahromi; Noor Ain Kamsani; Fakhrul Zaman Bin Rokhani; Roslina Bt Mohd Sidek; Shaiful Jahari Bin Hashim (Institute of Advanced Engineering and Science, 2022)
Due to the limitations of battery life and capacity, power supply has been the bottleneck for scaling of a wireless sensor network in thousands or millions of nodes. RF energy harvester (RFEH) is a promising solution to power up sensors and wireless devices due to increasing accessibility of RF energy sources, better silicon integration of the harvester circuit and compatibility with wireless networks. One of the significant limitations of RF energy harvester is low power efficiency rectifier where the main function of the micropower rectifier is to convert RF energy into DC energy. To achieve higher power conversion energy (PCE), this paper presents a five-stage charge pump rectifier, with implementation of diode-connected MOS transistors and an auxiliary circuit to produce compensation voltage to the charge pump to achieve higher efficiency over a wide input range. This work is designed and implemented using 130nm CMOS technology and achieved a wide input power range of 15 dBm with efficiency higher than 20%; and at -21 dBm sensitivity for 1V output is achieved while driving 1 MΩ load at 920MHz.